Autoreduction of cyanoferrate(III) ions in a polymer electrolyte membrane: all solid state electrochemical and spectroscopic investigations - Parthasarathy, Meera; Gopinath, Chinnakonda S.; Pillai, Vijayamohanan K. (Chemistry of Materials, 2006)
The effect of dielectric confinement on proton-coupled electron-transfer behavior and spectroscopic properties of cyanoferrate ions in a polymer electrolyte membrane (Nafion) has been investigated in an ``all-solid-state'' electrochemical cell, using techniques such as cyclic voltammetry, zero current chronopotentiometry, electrochemical impedance, diffuse reflectance infrared Fourier transform spectroscopy (DRIFT), UV-visible spectroscopy, X-ray photoelectron spectroscopy (XPS), and electron spin resonance spectroscopy (ESR). From the above investigations, we found that cyanoferrate(III) ions undergo autoreduction in the ionomer matrix, for which a sulfonate-coupled mechanism has been proposed. This report demonstrates the effectiveness of the micellar interface in tuning the redox potential of the confined ions. A systematic analysis of the cyclic voltammetry and impedance data for the [Fe(CN)(6)](4)(-)- containing Nafion membrane enables the estimation of a standard rate constant for [Fe(CN) 6](4-) oxidation, k(o), as 5.44 x 10(-6) cm/s and a diffusion coefficient, D-o, as 1.3 x 10(-12) cm(2)/s. A similar calculation yields a value of 4.8 x 10(-12) cm(2)/s for the diffusion coefficient of protons and 9.1 x 10(-6) cm/s for the standard rate constant for hydrogen oxidation. The similarity in mass-transfer coefficients calculated for protons and [Fe(CN)(6)](4-) ions suggests a proton-coupled electron-transfer mechanism for the [Fe(CN)(6)](4-)/[Fe(CN)(6)](3-) couple. The results of the above investigations could have direct technological relevance for deciding catalyst materials having redox compatibility with the polymer electrolyte, especially in the preparation of catalyst-coated membranes (wherein the fuel-cell catalyst is directly coated onto the polymer membrane instead of on the carbon support).

Field emission studies of novel ZnO nanostructures in high and low field regions - Ramgir, Niranjan S.; Late, Dattatray J.; Bhise, Ashok B.; Mulla, Imtiaz S.; More, Mahendra A.; Joag, Dilip S.; Pillai, Vijayamohanan K. (Nanotechnology, 2006)
A study of the field emission characteristics of novel structures of ZnO, namely marigolds, multipods and microbelts, has been carried out in both the close proximity configuration and the conventional field emission microscope. The use of a conventional field emission microscope overcomes the drawback of arc formation at high field values. The nonlinearity in the Fowler - Nordheim ( F - N) plot, a characteristic feature of semiconductors has been observed and explained on the basis of electron emission from both the conduction and the valence bands. The current stability exhibited by these structures is also promising for future device applications.

All-solid-state' electrochemistry of a protein-confined polymer electrolyte film - Parthasarathy, Meera; Pillai, Vijayamohanan K.; Mulla, Imtiaz S.; Shabab, Mohammed; Khan, Mohammad Islam (Biochemical and Biophysical Research Communications, 2007)
Interfacial redox behavior of a heme protein (hemoglobin) confined in a solid polymer electrolyte membrane, Nafion (a perfluoro sulfonic acid ionomer) is investigated using a unique `all-solid-state' electrochemical methodology. The supple phase-separated structure of the polymer electrolyte membrane, with hydrophilic pools containing solvated protons and water molecules, is found to preserve the incorporated protein in its active form even in the solid-state, using UV-visible, Fluorescence (of Tryptophan and Tyrosine residues) and DRIFT (diffuse reflectance infrared Fourier transform) spectroscopy. More specifically, solid-state cyclic voltammetry and electrochemical impedance of the protein-incorporated polymer films reveal that the Fe2+-form of the entrapped protein is found to bind molecular oxygen more strongly than the native protein. In the `all-solid-state' methodology, as there is no need to dip the protein-modified electrode in a liquid electrolyte (like the conventional electrochemical methods), it offers an easier means to study a number of proteins in a variety of polymer matrices (even biomimetic assemblies). In addition, the results of the present investigation could find interesting application in a variety of research disciplines, in addition to its fundamental scientific interest, including protein biotechnology, pharmaceutical and biomimetic chemistry. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: all-solid-state; cyclic voltammetry; hemoglobin; Impedance; Nafion; redox behavior

Energy analysis of field emitted electrons from a ZnO tetrapod - Al-Tabbakh, Ahmed A.; More, Mahendra A.; Joag, Dilip S.; Ramgir, Niranjan S.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (Applied Physics Letters, 2007)
The experimental total energy distribution (TED) of the field emitted electrons from a single pod of a ZnO tetrapod has been obtained, exhibiting a two-peak feature. The energy difference between the two peaks in the TED is found to be nearly equal to the band gap of the bulk ZnO. The results show that field emitted electrons originate from both the conduction and valence bands. The peak position dependence on the applied voltage has also been observed. In the present case, the size of the ZnO tetrapod is not small enough to reflect the quantum confinement effects.

Field emission investigations of RuO2-doped SnO2 wires - Bhise, Ashok B.; Late, Dattatray J.; Ramgir, Niranjan S.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Applied Surface Science, 2007)
Field emission studies of a bunch and a single isolated RuO2:SnO2 wire have been performed. A current density of 5.73 x 10(4) A/cm(2) is drawn from the single wire emitter at an applied field of 8.46 x 10(4) V/mu m. Nonlinearity in the Fowler-Nordheim (F-N) plot has been observed and explained on the basis of electron emission from both the conduction and the valence bands of the semiconductor. The current stability recorded at the preset value of 1.5 LA is observed to be good. Overall the high emission current density, good stability and mechanically robust nature of the RuO2:SnO2 wires offer advantages as field emitters for many potential applications. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: doped semiconductor; field emission; field enhancement factor; RuO2; SnO2

Surface-state-mediated electron transfer at nanostructured ZnO multipod/electrolyte interfaces - Parthasarathy, Meera; Ramgir, Niranjan S.; Sathe, Bhaskar R.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry C, 2007)
Redox kinetics of cyanoferrate(III) species adsorbed at an n-type ZnO multipod/electrolyte interface is explored using electrochemical techniques like cyclic voltammetry and impedance spectroscopy. The electrochemical impedance results are analyzed using a fluctuating energy level model, assuming isoenergetic tunneling of majority carriers through the Helmholtz layer. A shift in the slope of Mott-Schottky plots (C-sc(-2) versus E) together with evidence from cyclic voltammetry shows that the electron-transfer process is mediated by surface states formed because of the adsorption of ferricyanide ions (as evident from the results of Fourier transform infrared spectroscopy). More significantly, the pH of zero charge (point of zero zeta potential, pzzp) of ZnO multipods is found to be 4.5 (from capacitance vs pH plots) compared to that of bulk ZnO (pH 9.5), which could be explained on the basis of a lowering in the work function of the nanostructured semiconductor and its consequent susceptibility to the formation of surface states. This is in excellent agreement with our earlier observation of ultralow threshold field emission with this material in the light of the linear dependence of pzzp with work function of the electrode material. The flat-band potential of the nanostructures is found to be 200 mV more negative than that reported for bulk n-type ZnO electrodes, indicating a higher doping density in the former. A three-dimensional mapping of charge distribution in the surface states is attempted by correlating the capacitance response of the system subjected to a sinusoidal potential modulation to the semiconductor electrode with that resulting from a systematic variation of the redox potential of the dissolved acceptor (achieved by varying the pH of the electrolyte) which further reveals the polyenergetic nature of the surface states.

Template-assisted synthesis of ruthenium oxide nanoneedles: electrical and electrochemical properties - Subhramannia, Mahima; Balan, Beena K.; Sathe, Bhaskar R.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry C, 2007)
We here demonstrate the formation of bundles of RuO2 nanoneedles (ca. 100 nm diameter) by a templateassisted electrodeposition from aqueous RuCl3 solution under potentiostatic conditions at room temperature. Cyclic voltammetric measurements in 0.5 M H2SO4 show significantly higher redox-related charging behavior for the RuO2 nanoneedles compared to that of the commercial sample, which is also supported by the electrochemical impedance data. A comparison of the specific capacitance reveals a higher value for nanoneedles (3 F/g instead of 0.4 F/g for the bulk), which has been explained on the basis of enhanced reactivity. More interestingly, electrical transport measurements reveal a transition from metallic to semiconducting behavior especially at low-temperature caused by an impurity scattering mechanism. We anticipate that the present simple route for the fabrication of RuO2 nanostructures will be useful to exploit their potentials in various fields such as electrocatalysis, nanoelectronics, and more importantly for designing supercapacitors.

Efficient route towards the covalent functionalization of single walled carbon nanotubes - Kakade, Bhalchandra A.; Pillai, Vijayamohanan K. (Applied Surface Science, 2008)
A simple and efficient method of chemical functionalization of both single and multiwalled carbon nanotubes has been discussed to give enhanced water solubility by rapidly and efficiently generating an appreciable amount of hydrophilic functional groups using microwave radiation. Surface functionalization containing more than 30 wt% of oxygen has been achieved, resulting into solubility of 2-5 mg/mL. Further covalent functionalization of such soluble SWNTs provides a remarkable degree of aniline functionalization through amidation, where the formation of polyaniline has been avoided. Functionalization of SWNTs is confirmed by techniques like electron microscopy, Fourier transform infrared spectroscopy, thermogravimetry, Raman spectroscopy, cyclic voltammetry and impedance spectroscopy. Electrochemical analysis suggests an enhanced double layer capacitance (similar to 110 F/g) of nanotubes after microwave treatment. Aniline functionalization of SWNTs shows possible variations on the nanotube topography with concomitant formation of a dynamic polymer layer on the nanotube surface. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Carbon nanotubes; Functionalization; Microwave; solubility

Electrochemical sensing of sulphur dioxide: a comparison using dodecanethiol and citrate capped gold nanoclusters - Sathe, Bhaskar R.; Risbud, Mandar S.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (Journal of Nanoscience and Nanotechnology, 2008)
A comparison of cyclic voltammograms of dodecanethiol (DDT) capped Au nanoclusters (5.0 +/- 0.5 nm) and trisodium citrate (Cit) capped Au nanoclusters (similar to 10-15 nm) modified glassy carbon electrode shows a dramatic variation in the current when exposed to a small amount of sulphur dioxide. This is explained using the electrocatalytic properties of Au nanoclusters towards the oxidation of SO2, thus facilitating the fabrication of electrochemical sensors for the detection of SO2. The intrinsic redox changes observed for gold nanocluster-modified glassy carbon electrodes disappear on passing SO2, despite a dramatic current increase, which indeed scales up with the amount of dissolved SO2. Interestingly, a complete rejuvenation of the redox behavior of gold is also observed on subsequent removal of SO2 from the solution by passing pure nitrogen for 15 minutes. Further, these nanoclusters when characterized with X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared spectroscopy (FTIR) after SO2 passage reveal a variety of SO2 adsorption modes on gold surface. XP spectra also show a shift of 1.03 eV towards higher binding energy indicating a strong adsorption of SO2 gas, while FTIR gives conclusive evidence for the interaction of SO2 with gold nanoparticles.
Keywords: cyclic voltammetry; Fourier transform infrared spectroscopy; monolayer protected gold nanoclusters (Au-MPCs); SO2 sensor; X-ray photoelectron spectra

Enhanced field emission from hexagonal rhodium nanostructures - Sathe, Bhaskar R.; Kakade, Bhalchandra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Late, Dattatray J.; More, Mahendra A.; Joag, Dilip S. (Applied Physics Letters, 2008)
Shape selective synthesis of nanostructured Rh hexagons has been demonstrated with the help of a modified chemical vapor deposition using rhodium acetate. An ultralow threshold field of 0.72 V/mu m is observed to generate a field emission current density of 4 x 10(-3) mu A/cm(2). The high enhancement factor (9325) indicates that the origin of electron emission is from nanostructured features. The smaller size of emitting area, excellent current density, and stability over a period of more than 3 h are promising characteristics for the development of electron sources. (C) 2008 American Institute of Physics.

Highly selective catalytic hydrogenation of arenes using rhodium nanoparticles supported on multiwalled carbon nanotubes - Kakade, Bhalchandra A.; Sahoo, Suman; Halligudi, Shivappa B.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry C, 2008)
Rhodium nanoparticles (RhNPs; 4.9 +/- 0.4 nm) supported on multiwalled carbon nanotubes (Rh/MWNT), prepared by simple microwave treatment, show a remarkable catalytic activity for arene hydrogenation with enhanced turnover numbers of similar to 10000; disubstituted arenes show selective conversion of thermodynamically less favorable cis products (>80%). A series of arenes have been tested using various Rh-based catalysts, and a comparison of the results with that of reported rhodium catalysts shows unique selectivity under mild conditions.

High-purity synthesis of scrolled mats of multi-walled carbon nanotubes using temperature modulation - Kakade, Bhalchandra A.; Allouche, Hatem; Mahima, Subhramanyam; Sathe, Bhaskar R.; Pillai, Vijayamohanan K. (Carbon, 2008)
Felt-like mats (6-7 mu m thick) of multimalled carbon nanotubes wrapped into scrolls have been synthesized by chemical vapor deposition from a toluene-ferrocene mixture using a temperature ramp from 680 degrees C to 550 degrees C in hydrogen-argon atmosphere. Thermogravimetric analysis reveals a very low catalyst content of ca. 1.25 wt% in the as-synthesized sample while, X-ray photo electron and Raman spectroscopies suggest the results matching with that of multiwalled carbon nanotubes. Considering, different time scales of various reactions and the diffusion of different reactants and products a tentative base growth mechanism has been proposed as per the available characterization data in conjunction with possible scrolling effects. Thermal expansion effects could explain a tentative mechanism for rolling action of sheets. Interestingly, electrical conductivity measurements as a function of temperature suggest a semiconducting behavior, despite being governed by different electron transport mechanisms with activation energies of 0.33 and 1.03 meV corresponding to two temperature ranges respectively. Cyclic voltammetry and electrochemical impedance analysis show a reversible redox behavior due to very low catalyst content and an irreversible etching of the Fe catalyst after acid treatment. (C) 2007 Elsevier Ltd. All rights reserved.

Imaging the stomatal physiology of somatic embryo-derived peanut leaves by scanning electrochemical microscopy - Parthasarathy, Meera; Singh, Shweta; Hazra, Sulekha; Pillai, Vijayamohanan K. (Analytical and Bioanalytical Chemistry, 2008)
The stomatal physiology, chlorophyll distribution and photosynthetic activity of somatic embryo (SE)- and seedling-derived peanut plants grown in vitro (test tube-grown) and extra vitrum (soil-grown) are investigated using scanning electrochemical microscopy (SECM). This SECM imaging is performed in two different feedback modes, corresponding to oxygen evolution and chlorophyll distribution. More specifically, the oxygen evolution profiles of the in vitro leaves indicate important differences in leaf anatomy between the SE- and seedling-derived leaves. On the other hand, the chlorophyll distribution images show individual stomata of size ca. 27 +/- 5 mu m. Further studies on senescing (aged) leaves reveal interesting voltammograms that vary widely over the stomatal complexes and the surrounding tissues, probably due to the release of electroactive metabolites during chlorophyll breakdown when the leaves turn yellow. Thus, the present investigation could open up new opportunities for characterizing botanical systems using electroanalytical techniques. In addition, it could provide further insights into various areas of current relevance, including signal transduction, cell fate/differentiation and developmental biology.
Keywords: leaf senescence; oxygen evolution; photosynthesis; SECM; somatic embryogenesis; stomata

Invertase inhibition based electrochemical sensor for the detection of heavy metal ions in aqueous system: application of ultra-microlelectrode to enhance sucrose biosensor's sensitivity - Bagal-Kestwal, Dipali; Karve, Meena S.; Kakade, Bhalchandra A.; Pillai, Vijayamohanan K. (Biosensors & Bioelectronics, 2008)
We are reporting fabrication and characterization of electrochemical sucrose biosensor using ultra-microelectrode (UME) for the detection of heavy metal ions (Hg(II), Ag(I), Pb(II) and Cd(II)). The working UME, with 25 mu m diameter, was modified with invertase (INV, EC: 3.2.1.26) and glucose oxidase (GOD, EC: 1.1.3.4) entrapped in agarose-guar gum. The hydrophilic character of the agarose-guar gum composite matrix was checked by water contact angle measurement. The atomic force microscopy (AFM) images of the membranes showed proper confinement of both the enzymes during co-immobilization. The dynamic range for sucrose biosensor was achieved in the range of 1 x 10(-10) to 1 x 10(-7) M with lower detection limit 1 x 10(-10) M at pH 5.5 with 9 cycles of reuse. The spectrophotometric and electrochemical studies showed linear relationship between concentration of heavy metal ions and degree of inhibition of invertase. The toxicity sequence for invertase using both methods was observed as Hg(2+) > Pb(2+) > Ag(+) > Cd(2+). The dynamic linear range for mercury using electrochemical biosensor was observed in the range of 5 x 10(-10) to 12.5 x 10(-10) M for sucrose. The lower detection limit for the fabricated biosensor was found to be 5 x 10(-10) M. The reliability of the electrochemical biosensor was conformed by testing the spike samples and the results were comparable with the conventional photometric DNSA method. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Co-immobilization; Electrochemical biosensor; Heavy metal ions; Invertase (INV)-glucose oxidase (GOD); Mercury; Ultra-microelectrode (UME)

Polymer electrolyte fuel cells using nafion-based composite membranes with functionalized carbon nanotubes - Kannan, Ramaiyan; Kakade, Bhalchandra A.; Pillai, Vijayamohanan K. (Angewandte Chemie-International Edition, 2008)
Keywords: fuel cells; membranes; nanotubes; Polymers; proton transport

RuO(2) doped SnO(2) nanobipyramids on Si (100) as a field emitter - Bhise, Ashok B.; Late, Dattatray J.; Ramgir, Niranjan S.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Thin Solid Films, 2008)
Thin films of RuO(2): SnO(2) nanobipyramids have been grown on silicon (100) flat substrates, and their field emission behavior has been investigated. The field emission experiments have been performed in parallel plate configuration. In this experiment, the onset field for 0. 1 gA/ cm 2 current density has been found to be 0.2 V/mu m. The Fowler-Nordheim plot shows non-linear nature typical that of a semiconductor. The field enhancement factor has been estimated to be 35,600 cm(-1), indicating that the field emission originates from the nanometric features of the emitter. The current stability recorded at a preset value of I tA is observed to be good. Our field emission results on RuO(2): SnO(2) nanobipyramids indicate that, RuO(2): SnO(2) nanobipyramids are a potential candidate for futuristic field emission based devices. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: doped semiconductor; field emitter; field enhancement factor; ruthenium oxide; tin oxide

Shape-dependent electrocatalytic activity of platinum nanostructures - Subhramannia, Mahima; Pillai, Vijayamohanan K. (Journal of Materials Chemistry, 2008)
Since many metallic nanostructures with different shapes exhibit unique chemical and physical properties, a systematic attempt to synthesize these shape-controlled structures for property-shape correlation remains an important challenge in contemporary materials chemistry. Main difficulties like poor shape selectivity, low yield, presence of impurity phases, difficulty of separation, etc., are exacerbated since metallic structures have high surface energies which favour lower surface areas, and consequently many synthesis strategies, including the use of hard and soft templates and external nucleating agents, are being employed along with theoretical guidelines from density functional calculations on simpler systems. One of the important application areas where these structures have gained profound attention is in electrocatalysis, where the kinetics of many structure-sensitive reactions of technological relevance have been experimentally observed to show drastic changes with shape especially in the nanosize domain, at least in one dimension. Considering their scientific and technological importance, this feature article provides an overview of the recent progress on the shape-controlled synthesis of metallic nanostructures with special emphasis on platinum, and their crucial role in the electrocatalysis of anodic reactions for polymer electrolyte fuel cells.

Tuning the transport properties of Poly(oxyethylene)bisamine - Nafion polyelectrolyte complexes by dielectric manipulation - Parthasarathy, Meera; Kakade, Bhalchandra A.; Pillai, Vijayamohanan K. (Macromolecules, 2008)
Polyelectrolyte complexes (PECs) of Nafion-H+, a perfluorosulfonic acid ionomer, and Poly(oxyethylene)bisamine (Polyox) were synthesized, and the effect of electrostatic interactions on the physicochemical properties of the individual components was studied using a combination of spectroscopic and electrochemical techniques. More specifically, the pristine PECs were extensively characterized using viscosity, surface tension, and pH measurements and diffuse reflectance Fourier transform infrared (DRIFT) spectroscopy and their transport properties were investigated using cyclic voltammetry and electrochemical impedance spectroscopy, by employing [Fe(CN)(6)](3-) as a redox probe. Acid-base interaction between Nafion and Polyox is evident from pH measurements of the blend solutions, which indicate salt formation at a 50:50 composition, supported further by the existence of a maximum in the plot of surface tension versus blend composition. DRIFT spectra of the PEC membranes indicate subtle changes in the ionic environment and a transition from a state of medium hydration to a partially dehydrated state of the parent ionomer, Nation, after complexation with Polyox. Further evidence for polyelectrolyte-polyelectrolyte association is obtained from cyclic voltammetry, which shows that the interaction between the redox active chromophore, [Fe(CN)(6)](3-), and the pendent sulfonate groups of Nafion is minimized by complexation with the oppositely charged polyelectrolyte Polyox. The water-soluble nature of these PECs along with the tunable range of properties with blend composition could qualify them as suitable candidates for developing stimuli-responsive polymer systems for pharmaceutical and environmental applications.

Tuning the wetting properties of multiwalled carbon nanotubes by surface functionalization - Kakade, Bhalchandra A.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry C, 2008)
A simple strategy of chemical functionalization is employed here for controlling the wettability of multiwalled carbon nanotube films from superhydorphobic (156 degrees) to nearly hydrophilic (40 degrees), which further shows superhydrophilicity with a water contact angle of about 0 degrees within 2 s. The hydrophobic surface (water contact angle 145 degrees) in case of nitric-acid-treated MWCNT bucky paper shows an unusual pinning action even at a tilt angle of 45 degrees, following Wenzel behavior of the surface. The variation in the wetting properties of MWCNT bucky paper using such surface designing strategies provides controlled heterogeneity on the surface with no or minimal effect on surface roughness.

Domain size manipulation of perflouorinated polymer electrolytes by sulfonic acid-functionalized MWCNTs to enhance fuel cell performance - Kannan, Ramaiyan; Parthasarathy, Meera; Maraveedu, Sreekuttan U.; Kurungot, Sreekumar; Pillai, Vijayamohanan K. (Langmuir, 2009)
The application of sulfonic acid-functionalized multiwalled (s-MWNT) carbon nanotubes to manipulate the hydrophilic domain size of Nafion membranes is explored here as an option for tuning the proton conductivity of polymer electrolyte membranes for hydrogen-oxygen fuel cells. The electrochemical impedance experiments provide preliminary evidence of increased proton conductivity, while small-angle X-ray scattering measurements line. out enhanced ionic cluster domain size in these composite membranes as the central reason for higher conductivity (70 angstrom for the optimum composite membrane vs 50 angstrom for Nafion 115) values. Scanning electrochemical microscopy indicates synergistic interaction between the sulfonic acid functional groups present in the Nation membrane and those on the nanotube surface. More interestingly, the nanotube-tailored Nafion membranes ameliorate the performance of fuel cells as confirmed by measurements at a sin le-cell level, which reveal a maximum power density of 380 mW cm(-2), higher than those of Nafion 115 (250 mW cm(-2)) and recast Nafion (230 mW cm-2) membranes. Thus, in addition to providing an elegant means of controlling the ionic cluster size, the strategic approach of using CNT both as an anchoring backbone for -SO(3)H groups to enrich proton conductivity and as a blending agent to improve the mechanical characteristics of the Nafion phase might be helpful in alleviating many critical problems associated with the use of commercial Nafion membranes.

Field emission investigation of single Fe-doped SnO2 wire - Bhise, Ashok B.; Late, Dattatray J.; Sathe, Bhaskar R.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Solid State Sciences, 2009)
Tin oxide submicronwires doped with Fe element were prepared by the thermal evaporation method. Morphological and structural characterizations revealed wires with sub micron size and crystalline in nature. The field electron emission from the single Fe:SnO2 wire was carried out in conventional field emission microscope. The Fowler-Nordheim plot obtained from I-V characteristics of the wire showed a linear behavior typical that of metal. The field enhancement factor estimated from the slope of the F-N plot is 7455 cm(-1), indicating that the field emission is from nanometric features of the emitter. A current density of 10 A/cm(2) has been obtained at an applied field of 4.845 x 10(3) V/mu m. The field emission current-time record at a current level of 1 mu A for more than 3 h duration is promising for various field emissions based applications. (C) 2009 Published by Elsevier Masson SAS.
Keywords: Current stability; Fe doped; field emission; SnO2

Imaging hydrogen oxidation activity of catalyst-coated perfluoro sulfonic acid-polymer electrolyte membranes using scanning electrochemical microscopy - Parthasarathy, Meera; Pillai, Vijayamohanan K. (Journal of Chemical Sciences, 2009)
Scanning Electrochemical Microscopy (SECM) is a unique technique for studying fast heterogeneous kinetics and to map reactivity gradients along the surface of an electrocatalyst, especially when it involves multiple surface sites of varying reactivity. It combines the dual advantages offered by ultramicroelectrode (UME) voltammetry in terms of reduced ohmic drop and insignificant double layer charging contribution with the advantages of imaging by rastering the UME across an electro-active surface. In this work, we demonstrate these distinctive features of SECM in evaluating reactivity gradients on catalyst (Pt/C) coated NafionA (R) films towards hydrogen oxidation activity, a reaction of immense technological relevance. Imaging has been performed in the feedback mode by allowing H(2) evolution at the tip (25 A mu m Pt UME), which is reoxidized at the substrate electrode containing Pt/C-Nafion film. Interesting distribution in H(2) oxidation activity has been observed as a function of potential applied to the Pt/C-Nafion film. In addition, a plot of normalized tip current versus the substrate electrode potential indicates the effect of potential-induced reactivity change in the catalyst-coated membranes. The results of the present investigation are believed to be useful to H(2)/O(2) PEM fuel cells with respect to evaluating reactivity gradients of catalyst-coated polymer electrolyte membranes, which is important to rectify problems related to catalyst utilization.
Keywords: hydrogen oxidation; Imaging; Nafion; platinum; SECM

Preparation and characterization of rhodium nanostructures through the evolution of microgalvanic cells and their enhanced electrocatalytic activity for formaldehyde oxidation - Sathe, Bhaskar R.; Shinde, Dhanraj B.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry C, 2009)
Shape-controlled morphological evolution of nanostructured Rh has been demonstrated with the help of a galvanic displacement reaction using Al in 1 mM aqueous Rh(III) chloride at an open circuit potential 0.99 V and at a temperature of 273 K (room temperature). Nanospheres composed of small nanoparticles of size around 2.9 +/- 0.4 nm having uniform distribution with a FCC pattern have been evolved during the course of the reaction. Electrochemical results coupled with structural and morphological characterization data from transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray diffraction (XRD), and cyclic voltammetry (CV) suggested the formation of Rh nanostructures. Considering the role of the potential of substrate Al and Rh and diffusion of reactant and product species toward and from the surface of the Al, we proposed the tentative mechanism for the formation of microgalvanic cell. Significantly, these: rhodium nanostructures exhibit enhanced electrocatalytic activity toward many fuel cell reactions as demonstrated by formaldehyde oxidation in 0.5 M NaOH. The present strategy is expected to be valid for preparing many other similar electrocatalysts (Pt, Au, and Pd) capable of exhibiting such a remarkable size- and shape-dependent reactivity.

Synthesis of Sb-doped SnO2 nanowires and hyperbranched structures - Sathe, Bhaskar R.; Patil, Mrudula; Walke, Pravin S.; Vivek, J. P.; Lele, Ashish K.; Pillai, Vijayamohanan K.; Mulla, Imtiaz S. (Science of Advanced Materials, 2009)
Branched nanostructures of semiconducting materials are of great interest for their potential applications in optoelectronic, photonic devices and sensors. We herein describe a facile single-step chemical vapor deposition route for the synthesis of Sb-SnO2 hyperbranched nanostructures comprised of elongated nanowires with 30-40 nm diameter and 10-20 Am length. The morphology and structure has been characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), selective area electron diffraction (SAED), and powder X-ray diffraction (XRD). Also, a possible mechanism is proposed for the growth of nanowires into the hyperbranched form on the basis of the substrate effect, the role of Au nanoparticles, and the effect of Sb doping on specific morphology evolution. Interestingly, electrical conductivity measurements as a function of temperature suggest a semiconducting behavior, despite being governed by different electron-transport mechanisms with activation energies of 0.55 and 0.17 eV, which correspond to pure SnO2 and Sb-SnO2 nanowires, respectively. A precise control over the operating parameters not only envisages custom-designed, branched structures by a simple and economical route but also offers an alternative method to the expensive and tedious nanofabrication techniques for industrial applications.
Keywords: Au Nanoparticles; chemical vapor deposition; Sb-SnO2 Hyperbranched Nanostructures

Ultrafast switching time and third order nonlinear coefficients of microwave treated single walled carbon nanotube suspensions - Kamaraju, N.; Kumar, Sunil; Karthikeyan, B.; Kakade, Bhalchandra A.; Pillai, Vijayamohanan K.; Sood, A. K. (Journal of Nanoscience and Nanotechnology, 2009)
Microwave treated water soluble and amide functionalized single walled carbon nanotubes have been investigated using femtosecond degenerate pump-probe and nonlinear transmission experiments. The time resolved differential transmission using 75 femtosecond pulse with the central wavelength of 790 nm shows a bi-exponential ultrafast photo-bleaching with time constants of 160 fs (130 fs) and 920 fs (300 fs) for water soluble (amide functionalized) nanotubes. Open and closed aperture z-scans show saturation absorption and positive (negative) nonlinear refraction for water soluble (amide functionalized) nanotubes. Two photon absorption coefficient, beta(0) similar to 250 cm/GW (650 cm/GW) and nonlinear index, gamma similar to 15 cm(2)/pW (-30 cm(2)/pW) are obtained from the theoretical fit in the saturation limit to the data for two types of nanotubes.
Keywords: Nonlinear Optical Coefficients; SWCNT; Ultra-Fast Switching

Y-junction nanostructures of palladium: enhanced electrocatalytic properties for fuel cell reactions - Subhramannia, Mahima; Ramaiyan, Kannan; Aslam, Mohammed; Pillai, Vijayamohanan K. (Journal of Electroanalytical Chemistry, 2009)
Here we demonstrate the utility of hierarchically designed alumina templates for the formation of palladium Y-junction nanostructures through a chemical vapor deposition route. These structures exhibit enhanced electrocatalytic activity for the oxidation of formic acid (up to 1020%) compared to that of platinum Y-junction nanostructures, which could be of immense relevance to portable fuel cell technology, since designing a better electrocatalyst for fuel cell reactions continues to be an important challenge. Apart from the obvious applications in fuel cell electrocatalysis, these Y-junction nanostructures could also act as promising candidates for room temperature hydrogen separation and more importantly as interconnects in molecular scale electronic devices. The present method of fabrication of Y-junction nanostructures using hierarchical alumina templates could be extended to other metallic/semiconducting systems facilitating more general opportunities for such hierarchical designs in nanoelectronics. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: electrocatalysts; fuel cells; Hierarchical structures; Nanostructure; Porous alumina membrane; Y-junctions

Artificially designed membranes using phosphonated multiwall carbon nanotube-polybenzimidazole composites for polymer electrolyte fuel cells - Kannan, Ramaiyan; Aher, Pradnya P.; Palaniselvam, Thangavelu; Kurungot, Sreekumar; Kharul, Ulhas K.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry Letters, 2010)
The ability of phosphonated carbon nanotubes to offer an unprecedented approach to tune both proton-conductivity and mechanical stability of hybrid polymer electrolytes based on the polybenzimidazole membrane is demonstrated for fuel cell applications. The covalent attachment between the amino group of the 2-aminoethylphosphonic acid precursor and CNTs has been confirmed by NMR and IR experiments, while EDAX analysis indicates that one out of every 20 carbon atoms is in the CNT is functionalized. Proton conductivity of the composite membrane shows a remarkable 50% improvement in performance while a maximum power density of 780 and 600 mW cm(-2) is obtained for the composite and pristine membranes, respectively. Finally, the ultimate strength determined for the composite and pristine membranes is 100 and 65 MPa, respectively, demonstrating the superiority of the composite. This study opens up a new strategy to systematically tune the properties of polymer electrolytes for special applications by using appropriately functionalized CNTS.

Bio-inspired catalyst compositions for enhanced oxygen reduction using nanostructured Pt electrocatalysts in polymer electrolyte fuel cells - Parthasarathy, Meera; Kannan, Ramaiyan; Sreekumar, Kurungot; Pillai, Vijayamohanan K. (Journal of Materials Chemistry, 2010)
Composites of Nafion with a class of bio-molecules viz., plant hormones, are explored as potential polymer electrolytes for improving the proton transport inside the catalyst layer of a H(2)/O(2) fuel cell. Specifically, four nitrogenous plant hormones, two each from the class of auxins and cytokinins have been investigated, following preliminary characterization of the composite dispersions and membranes. Interestingly, the use of indole-3-acetic acid (an auxin) in the catalyst layer reveals a 30% enhancement in Pt catalyst utilization and improved fuel cell performance by 150 mW cm(-2). The effect of these bio-molecules on the kinetic and mass transport parameters has been analyzed systematically using a combination of electrochemical and spectroscopic techniques.

Effect of Fe3O4 on morphology of Fe-SnO2 hyperbranched heterostructures - Sathe, Bhaskar R.; Walke, Pravin S.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (Chemical Physics Letters, 2010)
A simple modified thermal evaporation technique is employed for the synthesis of microstructured Fe:SnO2 system and their plausible growth mechanism has been proposed based on the results from various characterization techniques. Such structures grow in two steps; initially, growth of Fe core takes place from Fe3O4 source which acts as nucleating site for SnO2 growth on its surface as per the vapor-liquid- solid progression. Moreover, the composition of Fe/Sn source and temperature are found to have key roles in governing their morphology. XPS studies clearly demonstrate the presence of Fe species, which acts as a catalyst along with source for hetero-structure growth with SnO2. (C) 2010 Published by Elsevier B.V.

Fabrication of In-doped SnO2 nanowire arrays and its field emission investigations - Bhise, Ashok B.; Late, Dattatray J.; Sathe, B.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Journal of Experimental Nanoscience, 2010)
The field emission of In-doped SnO2 wire array has been performed in parallel plate diode configuration. A maximum current density of 60 mu A/cm2 is drawn from the emitter at an applied field of 4 V/mu m. The nonlinearity in the Fowler-Nordheim plot, characteristics of semiconductor emitter has been observed and explained on the basis of electron emission from both the conduction and the valence bands. The current stability recorded at a preset value of 1 mu A is observed to be good. The high emission current density, good current stability and mechanically robust nature of the wires offer unprecedented advantages as promising cold cathodes for many potential applications based on field emission.
Keywords: cold cathodes; device; Doping; field emission; Nanowires; SnO2

Fowler-nordheim plot behavior and mechanism of field electron emission from ZnO tetrapod structures - Al-Tabbakh, Ahmed A.; More, Mahendra A.; Joag, Dilip S.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (ACS Nano, 2010)
Field emission measurements of current-voltage characteristics are reported for tetrapod structures of ZnO. The nonlinear Fowler-Nordheim (FN) plot is analyzed according to a model of calculation based on saturation of conduction band current and predominance of valence band current at high-field values. The simulated FN plot exhibits similar features to those observed experimentally. The model of calculation suggests that the slope variation of the FN plot, in the high-field and low-field regions, does not depend on the magnitude of saturation. Instead, it is a characteristic of the energy band structure and voltage-to-barrier-field conversion factor of the emitting material.
Keywords: field emission; Fowler-Nordheim plot; Nanostructures; nonlinearity; ZnO

High aspect ratio nanoscale multifunctional materials derived from hollow carbon nanofiber by polymer insertion and metal decoration - Balan, Beena K.; Kale, Vinayak S.; Aher, Pradnya P.; Shelke, Manjusha V.; Pillai, Vijayamohanan K.; Kurungot, Sreekumar (Chemical Communications, 2010)
A novel high aspect ratio material which can simultaneously display multiple functions such as proton and electron conductivity and electrocatalytic activity has been developed by incorporating both platinum nanoparticles and phosphoric acid doped polybenzimidazole along the inner and outer surfaces of a hollow carbon nanofiber.

High current density, low threshold field emission from functionalized carbon nanotube bucky paper - Kakade, Bhalchandra A.; Pillai, Vijayamohanan K.; Late, Dattatray J.; Chavan, Padmakar G.; Sheini, Farid J.; More, Mahendra A.; Joag, Dilip S. (Applied Physics Letters, 2010)
Field emission studies of bucky paper of multiwalled carbon nanotubes (MWNTs), prepared after microwave (MW) assisted acid functionalization are reported along with a comparison with that of ``as-grown'' sample. MW treated bucky papers reveal an interesting linear field emission behavior in Fowler-Nordheim plot. The field emission currents at preset value are found to be remarkably stable over a period of more than 3 h sustaining current densities of 4.9 mA/cm(2) and 8.5 mA/cm(2) for ``as-grown'' and functionalized sample, respectively. The enhancement in the field emission due to functionalization has been discussed in terms of tip opening and defect induced charge transport caused by intershell and intertubular interaction. (C) 2010 American Institute of Physics. [doi:10.1063/1.3479049]
Keywords: Carbon nanotubes; current density; field emission; fullerenes

High pt utilization electrodes for polymer electrolyte membrane fuel cells by dispersing pt particles formed by a preprecipitation method on carbon ``polished'' with polypyrrole - Unni, SreeKuttan M.; Dhavale, Vishal M.; Pillai, Vijayamohanan K.; Kurungot, Sreekumar (Journal of Physical Chemistry C, 2010)
Pt utilization on carbon black (CB) has been significantly improved by initially utilizing polypyrrole (PPy) as a moiety to ``polish'' the carbon surface and subsequently by dispersing Pt particles formed by a preprecipitation process to minimize their migration into the geometrically restricted areas of the carbon surface. This process strategy has helped to significantly extend the triple-phase boundary as a greater number of Pt particles comes in direct contact with Nafion, leading to a substantial improvement in the overall catalyst utilization. Preliminary analyses such as IR, thermogravimetric analysis, and N(2) sorption confirmed the presence of PPy on the surface. Approximately 50% reduction in the surface area of CB after the controlled in situ polymerization of pyrrole monomer on the carbon surface indicated preferential filling and coverage of pores and other geometrically restricted pockets of carbon surface. On the other hand, by converting Pt into colloids in the preprecipitation method prior to their reduction, the platinum particles are forced to stay on the hybrid support; a major part of which otherwise would have been migrated into the surface pores and defect sites. Platinum particle size on these hybrid supports is 2 times higher than the catalyst prepared by polyol process. However, the electroactive surface area and mass activity are 2 times higher than that of the Pt particles prepared by polyol on hybrid material and are also significantly higher than that of the conventional electrocatalysts prepared by the polyol method. At 0.8 V, the kinetic current density (j(k)) of Pt/C-PPy-Pre obtained from the Koutecky-Levich plot is 1.5 and 2.5 times higher than that of catalysts prepared by the polyol method on PPy-coated carbon and Vulcan XC-72 carbon, respectively. Almost 210 and 160 mW cm(-2) improvement for the maximum power density, respectively with oxygen and air, was obtained with the modified system in comparison to the conventional system when the single cell evaluations were carried out at 60 degrees C with a Pt loading of 0.5 mg cm(-2) in the anode and cathode sides. This enhancement in the cell performance under the two different oxygen partial pressure conditions clearly emphasizes the improved oxygen reduction reaction (ORR) and mass-transfer characteristics of the hybrid electrode material compared to the other catalysts.

Synthesis of Rh-carbon nanotube based heterostructures and their enhanced field emission characteristics - Sathe, Bhaskar R.; Kakade, Bhalchandra A.; Kushwaha, Ajay; Aslam, Mohammed; Pillai, Vijayamohanan K. (Chemical Communications, 2010)
Selective decoration of Rh nanospheres on acid functionalized carbon nanotubes has been demonstrated using Al as a sacrificial substrate. Remarkable field emission has been observed for this heterostructure as a high current density of 170 mu A cm(-2) is generated at an ultra-low threshold of 300 V mu m(-1), compared to much smaller values for Rh nanospheres and carbon nanotubes separately.

Carbon nanotube-modified sodium dodecyl sulfate-polyacrylamide gel electrophoresis for molecular weight determination of proteins - Parthasarathy, Meera; Debgupta, Joyashish; Kakade, Bhalchandra A.; Ansary, Abu Ayoobul; Khan, Mohammad Islam; Pillai, Vijayamohanan K. (Analytical Biochemistry, 2011)
The effect of incorporating carbon nanotubes (CNTs) in the gel matrix on the electrophoretic mobility of proteins based on their molecular weight differences was investigated using sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). More specifically, a reduction in standard deviation in the molecular weight calibration plots by 55% in the case of multiwalled carbon nanotubes (MWCNTs) and by 34% in the case of single-walled carbon nanotubes (SWCNTs) compared with that of pristine polyacrylamide gels was achieved after incorporating an insignificant amount of functionalized CNTs into the gel matrix. A mechanism based on a more uniform pore size distribution in CNT modified polyacrylamide gel matrix is proposed. Furthermore, the impact of SWCNTs and MWCNTs on the mobility of proteins in different molecular weight regimes at a given acrylamide concentration offers a tunable gel matrix in terms of the selection of molecular weight ranges of proteins. The robustness and excellent reproducibility of the CNT-PAGE protocol are expected to have a significant impact on the molecular weight determination of newly isolated proteins. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Carbon nanotubes; Gel electrophoresis; Molecular weight determination; Polyacrylamide; Protein separation

Competitive wetting of acetonitrile and dichloromethane in comparison to that of water on functionalized carbon nanotube surfaces - Debgupta, Joyashish; Kakade, Bhalchandra A.; Pillai, Vijayamohanan K. (Physical Chemistry Chemical Physics, 2011)
Differential wetting of pristine and ozonized carbon nanotubes has been studied using solvents like acetonitrile and dichloromethane in comparison to the well-known wetting behavior of water. Based on their unique structural and physical properties, functionalized CNT substrates have been used due to the fact that independent variation in molecular as well as electronic properties could be controlled by understanding the wetting of these liquids on carbon nanotubes (CNTs), both pristine as well as ozone treated. The sensitivity of the wetting behavior with respect to molecular interactions has been investigated using contact angle measurements while Raman and XPS studies unravel the differential wetting behavior. Charge-transfer between adsorbed molecules and CNTs has been identified to play a crucial role in determining the interfacial energies of these two liquids, especially in the case of acetonitrile. Ozone treatment has been observed to affect the surface properties of pristine CNTs along with a concomitant change in the wetting dynamics.

Electrochemical unzipping of multi-walled carbon nanotubes for facile synthesis of high-quality graphene nanoribbons - Shinde, Dhanraj B.; Debgupta, Joyashish; Kushwaha, Ajay; Aslam, Mohammed; Pillai, Vijayamohanan K. (Journal of the American Chemical Society, 2011)
Here we report a remarkable transformation of carbon nanotubes (CNTs) to nanoribbons composed of a few layers of graphene by a two-step electrochemical approach. This consists of the oxidation of CNTs at controlled potential, followed by reduction to form graphene nanoribbons (GNRs) having smooth edges and fewer defects, as evidenced by multiple characterization techniques, including Raman spectroscopy, atomic force microscopy, and transmission electron microscopy. This type of ``unzipping'' of CNTs (single-walled, multi-walled) in the presence of an interfacial electric field provides unique advantages with respect to the orientation of CNTs, which might make possible the production of GNRs with controlled widths and fewer defects.

Enhanced electrocatalytic performance of functionalized carbon nanotube electrodes for oxygen reduction in proton exchange membrane fuel cells - Kannan, Ramaiyan; Bipinlal, Unni; Kurungot, Sreekumar; Pillai, Vijayamohanan K. (Physical Chemistry Chemical Physics, 2011)
Although nitrogen doped CNTs (N-CNTs) are considered as a promising alternative to platinized carbon for the oxygen reduction reaction (ORR) in polymer electrolyte membrane fuel cells (PEMFCs), the origin of the enhanced ORR activity with N-CNTs is not clear at present. Among several plausible reasons, the exposure of edge plane and creation of impurity band/surface states near the Fermi level are considered as major causes behind the catalytic activity. However, CNTs without nitrogen doping are not known to catalyze the ORR. In this work, we study the ORR activity of functionalized carbon nanotubes with different functional groups, such as sulfonic acid and phosphonic acid, in order to understand the role of surface functionalities in catalyzing the reaction. Functionalized CNTs show significantly enhanced activity towards the ORR, while CNTs without such surface functional groups do not reveal any such special ORR activity. Linear sweep voltammetry experiments with different rotation rates show diffusion controlled limiting current values for functionalized CNTs, and the `n' values derived from Koutecky-Levich plots are 3.3 and 1.7 for S-MWCNTs and P-MWCNTs, respectively. This work demonstrates the ORR activity of functionalized MWCNTs, which opens up new strategies for electrocatalyst design in PEMFCs.

Enhanced electrocatalytic performance of interconnected Rh nano-chains towards formic acid oxidation - Sathe, Bhaskar R.; Balan, Beena K.; Pillai, Vijayamohanan K. (Energy & Environmental Science, 2011)
A chain-like assembly of rhodium nanoparticles (5-7 nm mean diameter) has been synthesized from rhodium chloride with the help of polydentate molecules like tartaric and ascorbic acids (1 : 3 in mM scale) as capping agents at room temperature. Subsequent characterization using transmission electron microscopy, X-ray diffraction and X-ray photoelectron spectroscopy reveals a unique inter-connected network like features, while their electrochemical behavior using cyclic voltammetry and current-time transient suggests potential applications as electrocatalysts in fuel cells. A significant negative shift in the onset potential as well as higher anodic peak current density for formic acid oxidation on Rh-tartaric acid (Rh-TA) as compared to that of bulk Rh metal confirms their higher electrocatalytic activity. Interestingly, the enhancement factor (R) with respect to that of bulk metallic Rh towards formic acid oxidation ranges up to 2000% for Rh-TA and 1200% for Rh-AA (Rh-ascorbic acid) respectively. The composition of Rh nano-chains has been further analyzed with thermogravimetry and Fourier transform infra-red spectroscopy to demonstrate the importance of controlling the chain topology using polyfunctional organic molecules. These findings open up new possibilities for tailoring nanostructured electrodes with potential benefits since the development of a better electrocatalysts for many fuel cell reactions continues to be an important challenge.

Ex-situ dispersion of core-shell nanoparticles of Cu-Pt on an in situ modified carbon surface and their enhanced electrocatalytic activities - Dhavale, Vishal M.; Unni, SreeKuttan M.; Kagalwala, Husain N.; Pillai, Vijayamohanan K.; Kurungot, Sreekumar (Chemical Communications, 2011)
Direct dispersion of core-shell nanoparticles on a carbon support (Cu@ Pt/C) has been achieved while retaining the essential core-shell features of the nanoparticles by adopting an in situ surface modification-cum-anchoring strategy.

Functionalization of SBA-15 mesoporous materials using ``thiol-ene click'' michael addition reaction - Kumari, Sushma; Malvi, Bharmana; Ganai, Anal Kumar; Pillai, Vijayamohanan K.; Sen Gupta, Sayam (Journal of Physical Chemistry C, 2011)
Methacrylate-labeled SBA-15 has been successfully synthesized from calcined SBA-15 and commercially available 3-trichlorosilyl propylmethacrylate. This material undergoes efficient thiol-ene ``click reaction'' with a variety of both thiol and disulfide-containing substrates in aqueous and organic media. The products were thoroughly characterized by a variety of analytical techniques including multinuclear (C-13, Si-29) solid-state NMR, TG-DTA, and nitrogen adsorption desorption studies. Disulfide-containing substrates in which the TCEP-mediated reduction of the disulfide bond and its subsequent addition to the methacrylate group anchored in SBA-15 in one-pot were used to synthesize a silica-protein hybrid material composed of biotin-labeled SBA-15 and streptavidin. Electrochemically active material was synthesized from the reaction of ferrocene-containing thiol and the methacrylate-labeled SBA-15. The ease of synthesis for the methacrylate-labeled SBA-15 material together with its ability to undergo efficient chemoselective thiol-ene reaction would make it a very attractive platform for the development of covalently anchored enzymes and sensors.

Improved performance of phosphonated carbon nanotube-polybenzimidazole composite membranes in proton exchange membrane fuel cells - Kannan, Ramaiyan; Kagalwala, Husain N.; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar; Pillai, Vijayamohanan K. (Journal of Materials Chemistry, 2011)
Development of thermally stable polymer electrolyte membranes with higher proton conductivity as well as mechanical stability is a key challenge in commercializing PEM fuel cells operating above 100 degrees C. Polybenzimidazole membranes are one of the promising candidates in this category although with limited mechanical stability and moderate proton conductivity. Here the incorporation of functionalized MWCNT is shown to increase both these key parameters of the polybenzimidazole membranes. Further, formation of a domain like structure after the incorporation of phosphonated MWCNTs (P-MWCNTs) in phosphoric acid doped polybenzimidazole membranes is demonstrated. The enhanced performance has been attributed to the formation of proton conducting networks that formed along the sidewalls of P-MWCNTs with a domain size of 17 nm as estimated from the small angle X-ray scattering measurements. Membrane electrode assembly (MEA) impedance measurements further reveal that the activation energy of oxygen reduction reaction (ORR) reduced for the composite membranes with enhanced proton conductivity. In addition, the mechanical strength measurements reveal a significant improvement in the yield strength and ultimate strength. Also, the mechanical strength of the composite membrane has been increased significantly as indicated by the improvement in the ultimate strength from 65 MPa to 100 MPa for the pristine and composite membranes, respectively. The optimum loading of P-MWCNTs is found to be 1% as inferred from the polarization measurements carried out using pure hydrogen and oxygen. Thus, this study provides a unique opportunity to tune the properties of polymer electrolytes to prepare application oriented hybrid membranes using CNTs with tailor-made functional groups.

Charge transport in functionalized multi-wall carbon nanotube-Nafion composite - Sangeeth, C. S. Suchand; Kannan, Ramaiyan; Pillai, Vijayamohanan K.; Menon, Reghu (Journal of Applied Physics, 2012)
The charge transport in sulfonated multi-wall carbon nanotube (sMWNT)-Nafion composite is reported. The scanning electron microscope images of the composite, at 1 and 10 wt % of sMWNT, show that the nanotubes are well dispersed in polymer matrix, with conductivity values of 0.005 and 3.2 S/cm, respectively; and the percolation threshold is nearly 0.42 wt. %. The exponent (similar to 0.25) of the temperature dependence of conductivity in both samples indicates Mott's variable range hopping (VRH) transport. The conductance in 1 wt. % sample increases by three orders of magnitude at high electric-fields, consistent with VRH model. The negative magnetoresistance in 10 wt. % sample is attributed to the forward interference scattering mechanism in VRH transport. The ac conductance in 1 wt. % sample is expressed by sigma(omega) proportional to omega(s), and the temperature dependence of s follows the correlated barrier hopping model. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4749264]

Electrochemical preparation of luminescent graphene quantum dots from multiwalled carbon nanotubes - Shinde, Dhanraj B.; Pillai, Vijayamohanan K. (Chemistry-A European Journal, 2012)
Green luminescent, graphene quantum dots (GQDs) with a uniform size of 3, 5, and 8.2(+/- 0.3) nm in diameter were prepared electrochemically from MWCNTs in propylene carbonate by using LiClO4 at 90?degrees C, whereas similar particles of 23(+/- 2) nm were obtained at 30?degrees C under identical conditions. Both these sets of GQDs displayed a remarkable quantum efficiency of 6.3 and 5.1?%, respectively. This method offers a novel strategy to synthesise size-tunable GQDs as evidenced by multiple characterisation techniques like transmission and scanning electron microscopy, atomic force microscopy, Raman spectroscopy and X-ray diffraction (XRD). Photoluminescence of these GQDs can be tailored by size variation through a systematic change in key process parameters, like diameter of carbon nanotube, electric field, concentration of supporting electrolyte and temperature. GQDs are promising candidates for a variety of applications, such as biomarkers, nanoelectronic devices and chemosensors due to their unique features, like high photostability, biocompatibility, nontoxicity and tunable solubility in water.
Keywords: electrochemical synthesis; graphene; Nanostructures; photoluminescence; quantum dots

Hydrous RuO2-carbon nanofiber electrodes with high mass and electrode-specific capacitance for efficient energy storage - Vellacheri, Ranjith; Pillai, Vijayamohanan K.; Kurungot, Sreekumar (Nanoscale, 2012)
We demonstrate a new strategy for the fabrication of supercapacitor electrodes possessing high mass and area-specific capacitance for efficient charge storage, which can be extremely useful for the development of light, compact and high performance supercapacitors for a variety of high power demanding applications. High mass and electrode area specific capacitances were attained by using Hydrous Ruthenium Oxide (HRO)-Carbon Nanofiber (CNF) hybrid electrodes prepared by the deposition of HRO (similar to 31% Ru content) on both the outer and inner surfaces of a cylindrical hollow CNF having open tips. Electrochemical studies of the uniformly deposited HRO nanoparticles on the CNF surface showed a mass specific capacitance of 645 F g(-1) and an electrode specific capacitance of 1.29 F cm(-2) with a HRO-CNF material loading of 2 mg cm(-2) in the supercapacitor electrodes. The mass specific capacitance of pure HRO is 301 F g(-1), whereas the mass specific capacitance of HRO in the HRO-CNF electrode is similar to 1300 F g(-1), which is very close to the theoretical capacitance of HRO. This enhanced charge storage ability, high rate capability, better cyclic stability and low ESR of the HRO-CNF will be useful for the development of high performance supercapacitors.

In situ electrochemical organization of CdSe nanoclusters on graphene during unzipping of carbon nanotubes - Debgupta, Joyashish; Shinde, Dhanraj B.; Pillai, Vijayamohanan K. (Chemical Communications, 2012)
In situ decoration of very small CdSe quantum dots on graphene nanoribbons (GNRs) has been achieved during the electrochemical unzipping of single walled carbon nanotubes. Critical parameters like the width of the GNRs, size distribution of quantum dots and their organization on GNRs have been shown to be strongly dependent on the electric field and time.

3-Dimensionally self-assembled single crystalline platinum nanostructures on few-layer graphene as an efficient oxygen reduction electrocatalyst - Unni, SreeKuttan M.; Pillai, Vijayamohanan K.; Kurungot, Sreekumar (RSC Advances, 2013)
Here, we report for the first time the synthesis of a 3-D self-assembled single crystalline platinum nanostructure directly on the graphene surface (PtNAGE) without using any harmful structural directing agents. A slow reduction method is used to prepare the desired platinum morphology. Initial formation of platinum nanoparticles and their homogenous dispersion on the surface of graphene have been observed 10 h after the commencement of the reduction using formic acid as the reducing agent. From these initially deposited seed particles, the growth starts on the {111} facets along the < 111 > direction and the nanostructure formation is completed within 72 h of the commencement of the reaction. The individual assembly has a diameter of similar to 80 nm. PtNAGE shows superior electrocatalytic activity towards oxygen reduction compared to graphene supported platinum (PtGE) and commercial carbon supported platinum (PtC) catalysts. PtNAGE is less vulnerable to strong hydroxyl adsorption compared to PtC and PtGE. Specific activity and mass activity of the catalyst are high compared to PtC by a factor of 6.50 and 1.80, respectively, and 4.00 and 3.05, respectively, compared to PtGE. The limiting current density of PtNAGE is 1.28 and 1.20 times higher than PtGE and PtC, respectively. Kinetic analysis of PtNAGE shows that the oxygen reduction reaction follows first order kinetics involving a four electron transfer mechanism with the direct formation of water. In addition to this, it has been observed that PtNAGE also prevents surface area degradation better than the commercial platinised carbon under potential induced conditions.

Electrochemical resolution of multiple redox events for graphene quantum dots - Shinde, Dhanraj B.; Pillai, Vijayamohanan K. (Angewandte Chemie-International Edition, 2013)
Keywords: charging energy; differential pulse voltammetry; graphene; quantum dots; single-electron transfer

Hysteresis and charge trapping in graphene quantum dots - Kalita, Hemen; Harikrishnan, V; Shinde, Dhanraj B.; Pillai, Vijayamohanan K.; Aslam, Mohammed (Applied Physics Letters, 2013)
We report current hysteresis in response to applied voltage in graphene quantum dots of average diameter 4.5 +/- 0.55 nm, synthesized electrochemically using multiwalled carbon nanotubes. In response to step voltages, transient current decay, characteristic of deep and shallow level charge traps with time constants 186 ms and 6 s, is observed. Discharging current transients indicate charge storage of the order of 100 mu C. Trap states are believed to arise due to the fast physisorption of external adsorbates, which are found to have a significant effect on charge transport and changes the resistance of the prepared device by an order of 3. (C) 2013 American Institute of Physics.

Stabilization of graphene quantum dots (GQDs) by encapsulation inside zeolitic imidazolate framework nanocrystals for photoluminescence tuning - Biswal, Bishnu P.; Shinde, Dhanraj B.; Pillai, Vijayamohanan K.; Banerjee, Rahul (Nanoscale, 2013)
Luminescent graphene quantum dots (GQDs) are encapsulated and stabilized in Zeolitic Imidazolate Framework (ZIF-8) nanocrystals. The GQDs are well confined due to the adsorption on the growing face of the ZIF-8 nanocrystals and have a profound effect on the shape of the nanocrystals from rhombic dodecahedron to spherical. Stabilizing GQDs inside the ZIF-8 nanocrystals results in tailoring of the photoluminescence emission (ca. 32 nm, bathochromic shift) of the GQD@ZIF-8 nanocrystal composite even after 3 months of aging under normal laboratory conditions. Also the water adsorption (at STP) capacity increased for the GQD@ ZIF-8 composite as compared to the pristine ZIF-8.

Structural and catalytic properties of a novel vanadium containing solid core mesoporous silica shell catalysts for gas phase oxidation reaction - Venkatathri, N.; Pillai, Vijayamohanan K.; Rajini, A.; Raju, M. Nooka; Reddy, I. A. K. (Journal of Chemical Sciences, 2013)
A novel vanadium containing solid core mesoporous silica shell catalyst was synthesized with different Si/V ratios by sol-gel method under neutral conditions. The synthesized materials were characterized by various techniques and gas phase diphenyl methane oxidation reaction. The mesoporosity combined with microporosity are formed by incorporation of octadecyltrichloro silane and triethylamine in the catalyst and it was found out from E-DAX and BET-surface area analysis. The material was found to be nanocrystalline. Vanadium is present as V4 + species in as-synthesized samples and convert to V5 + on calcination. Most of the vanadium is present in tetrahedral or square pyramidal environment. Incorporation of vanadium in silica framework was confirmed by Si-29 MAS NMR analysis. Among the various vanadium containing solid core mesoporous silica shell catalysts, the Si/V = 100 ratio exhibited maximum efficiency towards diphenyl methane to benzophenone gas phase reaction. The optimum condition required for maximum conversion and selectivity was found out from the catalytic studies.
Keywords: diphenylmethane; Gas phase oxidation; vanadium containing solid core mesoporous silica shell

Thiolated graphene - a new platform for anchoring CdSe quantum dots for hybrid heterostructures - Debgupta, Joyashish; Pillai, Vijayamohanan K. (Nanoscale, 2013)
Effective organization of small CdSe quantum dots on graphene sheets has been achieved by a simple solution exchange with thiol terminated graphene prepared by diazonium salt chemistry. This generic methodology of CdSe QD attachment to any graphene surface has remarkable implications in designing hybrid heterostructures.

Counter-ion dependent, longitudinal unzipping of multi-walled carbon nanotubes to highly conductive and transparent graphene nanoribbons - Shinde, Dhanraj B.; Majumder, Mainak; Pillai, Vijayamohanan K. (Scientific Reports, 2014)
Here we report for the first time, a simple hydrothermal approach for the bulk production of highly conductive and transparent graphene nanoribbons (GNRs) using several counter ions from K2SO4, KNO3, KOH and H2SO4 in aqueous media, where, selective intercalation followed by exfoliation gives highly conducting GNRs with over 80% yield. In these experiments, sulfate and nitrate ions act as a co-intercalant along with potassium ions resulting into exfoliation of multi-walled carbon nanotubes (MWCNTs) in an effective manner. The striking similarity of experimental results in KOH and H2SO4 that demonstrates partially damaged MWCNTs, implies that no individual K+, SO42- ion plays a key role in unwrapping of MWCNTs, rather this process is largely effective in the presence of both cations and anions working in a cooperative manner. The GNRs can be used for preparing conductive 16 k Omega sq(-1), transparent (82%) and flexible thin films using low cost fabrication method.

C@SiNW/TiO2 core-shell nanoarrays with sandwiched carbon passivation layer as high efficiency photoelectrode for water splitting - Devarapalli, Rami Reddy; Debgupta, Joyashish; Pillai, Vijayamohanan K.; Shelke, Manjusha V. (Scientific Reports, 2014)
One-dimensional heterostructure nanoarrays are efficiently promising as high performance electrodes for photo electrochemical (PEC) water splitting applications, wherein it is highly desirable for the electrode to have a broad light absorption, efficient charge separation and redox properties as well as defect free surface with high area suitable for fast interfacial charge transfer. We present highly active and unique photoelectrode for solar H-2 production, consisting of silicon nanowires (SiNWs)/TiO2 core-shell structures. SiNWs are passivated to reduce defect sites and protected against oxidation in air or water by forming very thin carbon layer sandwiched between SiNW and TiO2 surfaces. This carbon layer decreases recombination rates and also enhances the interfacial charge transfer between the silicon and TiO2. A systematic investigation of the role of SiNW length and TiO2 thickness on photocurrent reveals enhanced photocurrent density up to 5.97 mA/cm(2) at 1.0 V vs. NHE by using C@SiNW/TiO2 nanoarrays with photo electrochemical efficiency of 1.17%.

Electrochemical preparation of vertically aligned, hollow CdSe nanotubes and their p-n junction hybrids with electrodeposited Cu2O - Debgupta, Joyashish; Devarapalli, Rami Reddy; Rahman, Shakeelur; Shelke, Manjusha V.; Pillai, Vijayamohanan K. (Nanoscale, 2014)
Vertically aligned, hollow nanotubes of CdSe are grown on fluorine doped tin oxide (FTO) coated glass substrates by ZnO nanowire template-assisted electrodeposition technique, followed by selective removal of the ZnO core using NH4OH. A detailed mechanism of nucleation and anisotropic growth kinetics of nanotubes have been studied by a combination of characterization tools such as chronoamperometry, SEM and TEM. Interestingly, ``as grown'' CdSe nanotubes (CdSe NTs) on FTO coated glass plates behave as n-type semiconductors exhibiting an excellent photo-response (with a generated photocurrent density value of similar to 470 mu A cm(-2)) white in contact with p-type Cu2O (p-type semiconductor, grown separately on FTO plates) because of the formation of a n-p heterojunction (type II). The observed photoresponse is 3 times higher than that of a similar device prepared with electrodeposited CdSe films (not nanotubes) and Cu2P on FTO. This has been attributed to the hollow 1-D nature of CdSe NTs, which provides enhanced inner and outer surface areas for better absorption of light and also assists faster transport of photogenerated charge carriers.

Mitigating the cytotoxicity of graphene quantum dots and enhancing their applications in bioimaging and drug delivery - Chandra, Anil; Deshpande, Sonal; Shinde, Dhanraj B.; Pillai, Vijayamohanan K.; Singh, Neetu (ACS Macro Letters, 2014)
Despite the promising photophysical properties of fluorescent graphene quantum dots (GQDs), their cellular toxicity needs to be addressed before their full potential could be completely realized in biomedicine. A simple method for mitigating the toxicity of GQDs by embedding them in PEG matrix is reported here. The enhanced biocompatibility of polymer modified, P-GQDs, is attributed to reduced reactive oxygen species generation, as measured by an intracellular ROS assay. We also demonstrate the enhanced loading and efficient intracellular delivery of therapeutics by P-GQDs.

Sequential electrochemical unzipping of single-walled carbon nanotubes to graphene ribbons revealed by in situ Raman spectroscopy and imaging - John, Robin; Shinde, Dhanraj B.; Liu, Lili; Ding, Feng; Xu, Zhiping; Vijayan, Cherianath; Pillai, Vijayamohanan K.; Pradeep, Thalappil (ACS Nano, 2014)
We report an in situ Raman spectroscopic and microscopic investigation of the electrochemical unzipping of single-walled carbon nanotubes (SWNTs). Observations of the radial breathing modes (RBMs) using Raman spectral mapping reveal that metallic SWNTs are opened up rapidly followed by gradual unzipping of semiconducting SWNTs. Consideration of the resonant Raman scattering theory suggests that two metallic SWNTs with chiralities (10,4) and (12, 0) get unzipped first at a lower electrode potential (036 V) followed by the gradual unzipping of another two metallic tubes, (9, 3) and (10, 1), at a relatively higher potential (1.16 V). The semiconducting SWNTs with chiralities (11, 7) and (12, 5), however, get open up gradually at +/- 1.66 V. A rapid decrease followed by a subsequent gradual decrease in the metallicity of the SWNT ensemble as revealed from a remarkable variation of the peak width of the G band complies well with the variations of RBM. Cyclic voltammetry also gives direct evidence for unzipping in terms of improved capacitance after oxidation followed by more important removal of oxygen functionalities during the reduction step, as reflected in subtle changes of the morphology confirming the formation of graphene nanoribbons. The density functional-based tight binding calculations show additional dependence of chirality and diameter of nanotubes on the epoxide binding energies, which is in agreement with the Raman spectroscopic results and suggests a possible mechanism of unzipping determined by combined effects of the structural characteristics of SWNTs and applied field.
Keywords: density functional-based tight binding calculations; Electrochemistry; graphene; Raman spectral mapping; single-walled carbon nanotubes

Co3O4 nanorods-efficient non-noble metal electrocatalyst for oxygen evolution at neutral pH - Ramsundar, Rani M.; Debgupta, Joyashish; Pillai, Vijayamohanan K.; Joy, Pattayil Alias (Electrocatalysis, 2015)

Electrochemical preparation of nitrogen-doped graphene quantum dots and their size-dependent electrocatalytic activity for oxygen reduction - Shinde, Dhanraj B.; Dhavale, Vishal M.; Kurungot, Sreekumar; Pillai, Vijayamohanan K. (Bulletin of Materials Science, 2015)
Here we report a remarkable transformation of nitrogen-doped multiwalled carbon nanotubes (MWCNTs) to size selective nitrogen-doped graphene quantum dots (N-GQDs) by a two-step electrochemical method. The sizes of the N-GQDs strongly depend on the applied anodic potential, moreover increasing potential resulted in a smaller size of N-GQDs. These N-GQDs display many unusual size-dependant optoelectronic (blue emission) and electrocatalytic (oxygen reduction) properties. The presence of N dopants in the carbon framework not only causes faster unzipping of MWCNTs but also provides more low activation energy site for enhancing the electrocatalytic activity for technologically daunting reactions like oxygen reduction. The smaller size of N-GQDs has shown better performance as compared to the large N-GQDs. Interestingly, N-GQDs-3 (size = 2.5 +/- 0.3 nm, onset potential = 0.75 V) show a 30-mV higher positive onset potential shift compared to that of N-GQDs-2 (size = 4.7 +/- 0.3 nm, onset potential = 0.72 V) and 70 mV than that of N-GQDs-1 (size = 7.2 +/- 0.3, onset potential = 0.68 V) for oxygen reduction reaction (ORR) in a liquid phase. These result in the size-dependent electrocatalytic activity of N-GQDs for ORR as illustrated by the smaller sized N-GQDs (2.5 +/- 0.3 nm) undoubtedly promising metal-free electrocatalysts for fuel cell applications.
Keywords: fuel cells; MWCNTs; N-GQDs; oxygen reduction reaction; unzipping

Fractional photo-current dependence of graphene quantum dots prepared from carbon nanotubes - Kundu, Sumana; Ghosh, Sujoy; Fralaide, Michael; Narayanan, T. N.; Pillai, Vijayamohanan K.; Talapatra, Saikat (Physical Chemistry Chemical Physics, 2015)
We report on the photo-conductivity studies of chemically synthesized graphene quantum dots (GQDs) of average size 12 nm obtained by the oxidative acid treatment of MWCNTs. The dependence of photocurrent I-ph (I-ph = I-ill - I-dark) on the laser intensity P under a wide range of laser intensities (5 mW <= P <= 60 mW) shows a fractional power dependence of I-ph on light intensity. The temperature dependence (300 K < T < 50 K) of I-ph observed in thin films of these GQDs indicates that in the higher temperature region (T > similar to 100 K), as the temperature increases, the number of thermally generated carriers increase resulting in increased I-ph. At sufficiently low temperatures (T <= 100 K), a constant I-ph is observed, indicating a constant photocarrier density. Such a behavior is typically observed in many photoactive disordered semiconductors, which are often used in a variety of applications. We believe that the investigations presented here will enhance our understanding of the photocurrent generation phenomenon in chemically obtained GQDs.

Graphene nanoribbons as prospective field emitter - Khare, Ruchita T.; Shinde, Dhanraj B.; Bansode, Sanjeewani; More, Mahendra A.; Majumder, Mainak; Pillai, Vijayamohanan K.; Late, Dattatray J. (Applied Physics Letters, 2015)
Field emission characteristics of graphene nanoribbons (GNRs) synthesized by unzipping of multiwall carbon nanotubes using a facile hydrothermal route have been investigated at a base pressure of 1 x 10(-8) mbar. The values of turn-on field, required to draw an emission current densities of 1 and 10 mu A/cm(2), are found to be 2.8 and 5.8 V/mu m, respectively, and a maximum emission current density of 500 mu A/cm(2) has been drawn at an applied field of 9.8 V/mu m. The emission current stability of the GNRs emitter was studied at preset values of 1 and 10 mu A over a period of 3 h, and is found to be excellent. The field emission results demonstrated herein suggest that GNRs based field emitters can open up many opportunities for their potential utilization as large area field emitters in various vacuum micro-nanoelectronic devices such as flexible field emission displays, portable X-ray, and microwave tubes. (C) 2015 AIP Publishing LLC.

Role of the molecular structure of carboxylate-alumoxanes in the enhanced nucleation of polypropylene - Mani, Mohan Raj; Chellaswamy, Ramesh; Marathe, Yogesh N.; Pillai, Vijayamohanan K. (Chemical Communications, 2015)
We have reported the use of carboxylate-alumoxanes as efficient nucleating agents for isotactic polypropylene (iPP) with a possible structural correlation to the nucleation efficiency. The unique, butterfly-like structure of carboxylate-alumoxanes correlates well with the nucleation characteristics of iPP and, for the first time, the impact of a thermally induced, crystalline transition of carboxylate-alumoxanes, which alters neither the structural conformation nor the nucleation efficiency of the transformed material, is demonstrated.

Synthesis of N, F and S co-doped graphene quantum dots - Kundu, Sumana; Yadav, Ram Manohar; Narayanan, T. N.; Shelke, Manjusha V.; Vajtai, Robert; Ajayan, Pulickel M.; Pillai, Vijayamohanan K. (Nanoscale, 2015)
Graphene quantum dots (GQDs) are a promising category of materials with remarkable size dependent properties like tunable bandgap and photoluminescence along with the possibility of effective chemical functionalization. Doping of GQDs with heteroatoms is an interesting way of regulating their properties. Herein, we report a facile and scalable one-step synthesis of luminescent GQDs, substitutionally co-doped with N, F and S, of similar to 2 nm average size by a microwave treatment of multi-walled carbon nanotubes in a customized ionic liquid medium. The use of an ionic liquid coupled with the use of a microwave technique enables not only an ultrafast process for the synthesis of co-doped GQDs, but also provides excellent photoluminescence quantum yield (70%), perhaps due to the interaction of defect clusters and dopants.

Enhanced nucleation of polypropylene by metal-organic frameworks (MOFs) based on aluminium dicarboxylates: influence of structural features - Mani, Mohan Raj; Chellaswamy, Ramesh; Marathe, Yogesh N.; Pillai, Vijayamohanan K. (RSC Advances, 2016)
Metal-organic frameworks (MOFs) based on aluminium dicarboxylates provide a new platform for the enhanced nucleation of isotactic polypropylene (iPP). For instance, aluminium dicarboxylates exhibit a unique butterfly-like structure similar to that of carboxylate-alumoxanes and correlates well with the nucleation characteristics of iPP. A subtle change in the structure of the ligand backbone (fumarate/succinate) does not alter the framework structure despite changing the hydrophilic/hydrophobic character and its subsequent nucleation characteristics. This suggests that the nucleating agent should facilitate favourable interaction with hydrophobic iPP for efficient nucleation. Further, a systematic variation of the alkyl chain length in the Al-dicarboxylate does not change the nucleation efficiency considerably, even though it increases the distance between the octahedral alumina chains in the metal-organic framework, suggesting that the butterfly-like structure present in the framework is a key aspect for nucleation. Finally, the significance of the orientational conformation of the dicarboxylate around the metal centre for the nucleation is confirmed by the poor nucleation efficiency of chromium and zirconium suberate MOFs where the orientation of suberate would be different from that of aluminium suberate due to the difference in the ligation of the carboxylate group. The present work thus provides valuable pathways for developing new nucleating agents based on MOFs with appropriate selection and orientation of the organic linkers around the metal centre.

Facile green synthesis of BCN nanosheets as high-performance electrode material for electrochemical energy storage - Karbhal, Indrapal; Devarapalli, Rami Reddy; Debgupta, Joyashish; Pillai, Vijayamohanan K.; Ajayan, Pulickel M.; Shelke, Manjusha V. (Chemistry-A European Journal, 2016)
Two-dimensional hexagonal boron carbon nitride (BCN) nanosheets (NSs) were synthesized by new approach in which a mixture of glucose and an adduct of boric acid (H3BO3) and urea (NH2CONH2) is heated at 900 degrees C. The method is green, scalable and gives a high yield of BCN NSs with average size of about 1 mm and thickness of about 13 nm. Structural characterization of the as-synthesized material was carried out by several techniques, and its energy-storage properties were evaluated electrochemically. The material showed excellent capacitive behaviour with a specific capacitance as high as 244 F g(-1) at a current density of 1 A g(-1). The material retains up to 96% of its initial capacity after 3000 cycles at a current density of 5 A g(-1).
Keywords: boron; Doping; Electrochemistry; Nanoparticles; nitrides

New understanding on regulating the crystallization and morphology of the beta-polymorph of isotactic polypropylene based on carboxylate-alumoxane nucleating agents - Mani, Mohan Raj; Chellaswamy, Ramesh; Marathe, Yogesh N.; Pillai, Vijayamohanan K. (Macromolecules, 2016)
Carboxylate alumoxane derived from p-n-alkylbenzoic acids, where n-alkyl group changes from 2 to 8 carbon atoms, exhibits dual nucleating ability and nucleates isotactic polypropylene (iPP) into predominantly in the beta-phase under specific conditions. The selectivity of the beta-phase nucleation depends on the concentration of the nucleating agent, end melting temperature and cooling rate. The beta-phase obtained from p-n-alkylbenzoate-alumoxanes is compared with the beta-phase obtained from calcium pimelate (CaP), an efficient beta-phase selective, nucleating agent, using the results from DSC, WAXS, and SAXS analysis. The lamellar morphology of iPP nucleated with different nucleating agents crystallized at different crystallization temperatures (T-C) under controlled nonisothermal conditions are evaluated using SAXS analysis. The long period increases with increasing crystallization temperature and the long period of the beta-phase is always larger than that of the alpha-phase for a given crystallization temperature. Furthermore, the variation of long period with crystallization temperature clearly brings out two crystallization temperature ranges; the low temperature range and the high temperature range. However, the beta-phase shows a lower changeover temperature compared to that of the alpha-phase. The one-dimensional correlation analysis of the beta-phase shows that the thickness of the crystal lamellae (lc) increases with T-C and exhibits the low and high crystallization temperature ranges, while the thickness, of the amorphous layer (la) more or less remains constant. In-situ high temperature WAXS studies capture the beta-phase to the a-phase transition and the transformed material con-elates well with the lamellar thickness of the beta-phase. The morphological difference between the alpha- and the beta-phases are discussed and attributed to the differences in the impact properties and the melting temperature. This study clearly demonstrates that the lamellar morphology mainly depends on the T-C and not on the nature of the nucleating agents.

Role of structural distortion in stabilizing electrosynthesized blue emitting phosphorene quantum dots - Valappil, Manila Ozhukil; Joshi, Krati; John, Lisa; Krishnamurthy, Sailaja; Jana, Bikash; Patra, Amitava; Pillai, Vijayamohanan K.; Alwarappan, Subbiah (Journal of Physical Chemistry Letters, 2019)
Luminescent phosphorene quantum dots (PQDs) have emerged as fascinating nanomaterials for potential applications in optoelectronics, catalysis, and sensing. Herein, we investigate the structural distortion of black phosphorus (BP) under an applied electric field to yield blue luminescent PQDs [average diameter 8 +/- 1.5 nm (N = 60)]. The electrosynthesized PQDs exhibit photoluminescence emission independent of excitation wavelength with 84% quantum efficiency. Structural distortion that occurred during the transformation of BP to PQDs is confirmed by results obtained during transmission electron microscopy, X-ray diffraction and X-ray photoelectron spectroscopy. Further, using first-principles-based density functional theory, calculations on oxygenated and nonoxygenated PQDs augment the experimental observations that an optimum oxygen content maintains the structural integrity of PQDs, above which the structural robustness of PQDs is drastically diminished.